A closed-form analysis of fading envelope correlation across a wideband basestation array. - Roy, S. (IEEE Transactions on wireless communications)
This letter proposes a simple analytical model to accurately quantify the degree of fading envelope correlation among the received signals at the antenna elements of an adaptive array operating in a frequency-selective environment. The adaptive array is assumed to be at an elevated base station with scattering being confined to a local region around the subscriber station. This corresponds to the so-called "local scattering" or "macrocell" assumption and it results in most of the received energy at the base station array being concentrated within a given beamwidth. Our formulation provides closed-form, finite sum expressions for the covariance and correlation coefficients as a function of spatial and frequency separation.